An empirical research of the creative process of collaborative e-business capability in service industry. (1st January 2012) - Jiang, Yi; Zhao, Jing
In the service industry, the creative process of a firm's collaborative e-business capability has already become the key focus of enterprises and academic circles. From the view of e-business process, this paper, together with the theory of resource-based view (RBV), demonstrates the formation of collaborative e-business capability in the e-CRM process. We find that the integration of IT resources is the foundation for the creation of e-business capability and IT knowledge integration capability, serving as a kind of internal e-business capability, and fully mediates the creation of collaborative e-business capability. This study is expected to help managers in planning internal and external resources and make contributions to the research perspective on e-business capability.